Distal Aortic Arch Hypoplasia and Coarctation Repair: A Tailored Enlargement Technique. Issue 5 (September 2018) - Poncelet, Alain J.; Henkens, Arnaud; Sluysmans, Thierry; Moniotte, Stephane; de Beco, Geoffroy; Momeni, Mona; Detaille, Thierry; Rubay, Jean E.
Background: Several techniques have been described to correct coarctation associated with distal arch hypoplasia. However, in neonates, residual gradients are frequently encountered and influence long-term outcome. We reviewed our experience with an alternative technique of repair combining carotid–subclavian angioplasty and extended end-to-end anastomosis. Methods: From 1998 through 2014, 109 neonates (median age, 9 days) with coarctation and distal arch hypoplasia (n = 106) or type A interrupted aortic arch (n = 3) underwent repair using this technique. Thirty patients had isolated lesions (group 1), 44 associated ventricular septal defect (group 2), and 35 associated complex cardiac lesions (group 3). Median follow-up was 98 months. Results: Repair was performed via left thoracotomy in 97%. There was one procedural-related death (0.9%) and overall five patients died during index admission (4.6%). Ten deaths were recorded at follow-up. Actuarial five-year survival was 86% (100% in group 1, 91% group 2, and 66% in group 3). Recurrent coarctation (clinical or invasive gradient >20 mm Hg) developed in 15 patients, all but 2 successfully treated by balloon dilatation. Freedom from any reintervention (dilatation or surgery) at five years was 86%. Only two patients were on antihypertensive drugs at last follow-up. Conclusions: This combined technique to correct distal arch hypoplasia and isthmic coarctation results in low mortality and acceptable recurrence rate. It preserves the left subclavian artery and allows enlargement of the distal arch diameter. Late outcome is excellent with very low prevalence of late arterial hypertension.